PERBEDAAN KEKUATAN FLEXURAL ANTARA FIBER REINFORCED COMPOSITE DENGAN FIBER SISAL (Agave sisalana) TERALKALISASI DAN NON-ALKALISASI - , YOGI GLADI PRAYUDI, Prof. Dr. drg. Widjijono, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fiber reinforced composite (FRC) is a composite material consisting of a matrix and fiber. One type of natural fiber is sisal fiber (Agave sisalana). Sisal fiber contains hemicelluloses, lignin and pectin, those that cause poor adhesion between matrix and fiber. Therefore, it needs an alkalization treatment. The purpose of this study was to determine the difference between the flexural strength of FRC with alkalized sisal fiber and the one with non-alkalized sisal fiber. The main materials of this research were sisal fiber (Balittas, Indonesia) and flowable Composite (Masterflow, Brazil). The research sample was a fiber bar with the size of (25x2x2) mm. The sample consisted of two groups, FRC with alkalized sisal fiber and FRC with non-alkalized fiber with four bars in each group. The samples of Group 1 were created using FRC with sisal fiber that had been alkalized. The alkalization process was done by soaking the sisal fiber in 5% NaOH solution for 4 hours and then dried in an oven at a temperature of 80° C for 24 hours. Group 2, as a control group, had the sample made without alkalization. Flexural strength was measured using a universal testing machine at 1 mm /minute. The data were then tested using independent t-test (α = 0.05). The results showed that the average flexural strength of FRC with alkalized sisal fiber was 64.31 ± 1.61 MPa and that with non-alkalized fiber was 41.15 ± 1.07 MPa. The results of the independent t-test showed a significant difference between the flexural strength of FRC with alkalized sisal fiber and the one with non-alkalized fiber (p <0.05). Thus, the flexural strength of fiber-reinforced composite with alkalized sisal fiber was higher than the non-alkalized one. Keyword: Sisal fiber, flexural strength, alkalization, FRC